IMPROVING ORAL HYGIENE STATUS IN CHILDREN WITH AUTISM SPECTRUM DISORDER IN BANDUNG THROUGH EDUCATION USING “TOOTH BRUSHING VISUAL PEDAGOGY” FLIPCHART - Josevinda Ayu Pramesti; Sri Susilawati; Inne Suherna Sasmita (Syntax Corporation Indonesia, 2023)
Background: Autism Spectrum Disorder (ASD) is characterized by social communication deficits and restricted interests. Children with ASD face challenges in oral health, necessitating education. Education with visual pedagogy using “Tooth Brushing Visual Pedagogy” flipchart can be used to improve dental health in ASD children. Purpose: This study examined the effectiveness of the